2020
DOI: 10.1186/s40635-020-00339-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic characteristics of 11 formulae for calculating corrected flow time as measured by a wearable Doppler patch

Abstract: Background Change of the corrected flow time (Ftc) is a surrogate for tracking stroke volume (SV) in the intensive care unit. Multiple Ftc equations have been proposed; many have not had their diagnostic characteristics for detecting SV change reported. Further, little is known about the inherent Ftc variability induced by the respiratory cycle. Materials and methods Using a wearable Doppler ultrasound patch, we studied the clinical performance of 11 Ftc equations to detect a 10% change in SV measured by non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 39 publications
(60 reference statements)
7
43
0
Order By: Relevance
“…In addition, there were little differences between FTc 6 and FTc 10 . However, a recent study showed that the respiratory cycle could induce a variation in FTc [ 28 ]. This could affect the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there were little differences between FTc 6 and FTc 10 . However, a recent study showed that the respiratory cycle could induce a variation in FTc [ 28 ]. This could affect the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all clinical studies have replicated these findings 36 . One contributing factor to these discrepancies may be the small number of beats sampled (e.g., 1–3) used to calculate blood flow metrics coupled with normal, inherent VTI variation introduced by the respiratory cycle 37 39 . The hands-free CW Doppler patch is well-suited to overcome this potential source of variability by acquiring continuous measurements over many beats 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the number of beats sampled varies as a function of CV and the threshold to detect. For example, detecting a 3% change in FTc ( 6 ) with a CV of 4.5% demands roughly 36 beats sampled before and after an intervention.…”
Section: Discussionmentioning
confidence: 99%
“…It was placed by palpation below the angle of the jaw; when an audible Doppler shift and spectrogram consistent with the common carotid artery were obtained, the patch was adhered to the neck. The duration of systole, in seconds, was used to calculate the corrected flow time (FTc), as described previously ( 5 , 6 ).…”
Section: Methodsmentioning
confidence: 99%